Met Office Unified Model high‐resolution simulations of a strong wind event in Antarctica. (14th February 2014) - Orr, Andrew; Phillips, Tony; Webster, Stuart; Elvidge, Andy; Weeks, Mark; Hosking, Scott; Turner, John
<x xml:space="preserve">Abstract</x> During winter much of the Antarctic coast is susceptible to severe and hazardous strong‐wind events (SWEs) associated with the enhancement of katabatic winds by synoptic weather systems. In this study a SWE that occurred at Mawson, East Antarctica, involving a hurricane force wind speed of ∼39 m s−1 is simulated by the Met Office Unified Model at high horizontal resolutions with grid lengths between 12 and 1.5 km. It is shown that all the simulations capture the qualitative evolution of the SWE but underestimate its peak wind speed. The extent of the underestimate is dependent on horizontal resolution, with the 4 and 1.5 km (12 km) models underforecasting the peak wind speed by around 15% (36%). In addition to a strengthening of the katabatic flow, the simulated low‐level cyclonic winds associated with the depression responsible for the SWE caused the formation of a barrier‐type jet parallel to the coast, resulting in strong wind convergence/interaction at the coastline and suggesting a strong topographic influence on the dynamics responsible for SWE formation. Moreover, it suggests that Mawson is influenced by small‐scale gravity waves that formed in response to the stronger winds, and that representation of this was particularly sensitive to horizontal resolution. Additional experiments suggest that the Met Office Unified Model simulation of the SWE is most sensitive to the representation of turbulent mixing under stable conditions. This study is important to identify shortcomings in the performance of the Met Office Unified Model near Antarctica's coastal regions as well as to improve understanding of the processes responsible for SWEs.